2013
DOI: 10.4187/respcare.02187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Transforming Growth Factor β1 and Tumor Necrosis Factor α Is Associated With Asthma and Modulates the Severity of Asthma

Abstract: BACKGROUND: The role of transforming growth factor ␤1 (TGF-␤1) and tumor necrosis factor ␣ (TNF-␣) in asthma is unclear. The aim of this study was to assess the relationships among polymorphisms, clinical phenotypes, and the serum levels of TGF-␤1 and TNF-␣. METHODS: Polymorphisms of promoter of TGF-␤1 (C-509T locus) and TNF-␣ (G-308 A locus; rs 1800629) in 217 asthmatic patients and 110 healthy controls were evaluated. Pulmonary function, total immunoglobulin E (IgE), specific IgE antibodies, total eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Previous studies identified polymorphisms in the TGFβ1 locus that segregate with allergy and asthma (3337). The suspicion that TGFβ1 might contribute to allergic disease prompted investigations into its effects on IgE-mediated mast cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified polymorphisms in the TGFβ1 locus that segregate with allergy and asthma (3337). The suspicion that TGFβ1 might contribute to allergic disease prompted investigations into its effects on IgE-mediated mast cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Gene polymorphisms in the TGF-ß1 promoter region are associated with the development of asthma [9,132]. Several single nucleotide polymorphisms (SNPs) are associated with peripheral blood eosinophilia in asthmatic patients [133].…”
Section: Genetic Tgf-ß Modifiersmentioning
confidence: 99%
“…MAPK signaling pathways are known to be involved in airway inflammation and the regulation of immune cells, which are the hallmark features of asthma [49,50,53]. In addition, genetic variants of MAPK1 might be involved in regulating cytokine levels in asthma patients, which might modulate the severity of asthma [54][55][56].…”
Section: Discussionmentioning
confidence: 99%